The Commonwealth of Independent States as a Way to a «Civilized Divorce» - V. G. Burkov; K. E. Mescheryakov; R. G. Shamgunov (Евразийская интеграция: экономика, право, политика, 2019)
The article describes the events, which took place in the USSR in its last years. It discovers the reasons for the collapse of the Soviet Union and the establishment of the Commonwealth of Independent States. It explains why the CIS did not grow in a new Union state and did become nothing more than a mechanism for a «civilized divorce» of the former Soviet republics.